Semantic decomposition vs componential analysis from functional-semantic veiw - Mykhaylenko, V. V.; Михайленко, Валерій Васильович; Михайленко, В. В. (Одеса, 2017)
У фокусі статті - семантична структура прикметника «rich» у системі мови та структурі дискурсу. Компонентний аналіз є інструментом лексичної семантики, а семантична декомпозиція - інструментом функціональної семантики.

The present paper is focused on the semantic structure of the adjective "rich" in language system and discourse structure. Сompo- nential analysis is an instrument of Lexical Semantics, while Semantic Decomposition - in Functional Semantics.
Mykhaylenko, V. V. Semantic decomposition vs componential analysis from functional-semantic veiw / V. V. Mykhaylenko // Одеський лінгвістичний вісник. – 2017. – Вип. 10. – Т.1. – С. 80-84.
Keywords: Research Subject Categories::HUMANITIES and RELIGION; лексична семантика; функціональна семантика; прикметник; компонентний аналіз; декомпозиція; компонент; lexical semantics; functional semantics; adjective; componential analysis; decomposition; component